Educational Rights For Children With Special Needs Through Joint Monitoring In Inclusive Education - Fatriani, Fenny; Nurhayani, Neng Yani (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2022)
This study aims to analyze the role of inclusive education in increasing access to education and improving the quality of educational services for Children with Special Needs (ABK) as mandated by the Minister of National Education Number 70 of 2009. This research uses a descriptive-analytical method with a case study approach at SD Sains Al Biruni Bandung, the first inclusion school in Bandung. The focus of this study is on community participation, which includes the involvement of parents and accompanying teachers who are directly related to Children with Special Needs (ABK). The results showed that parental involvement and support could be seen in the admission process of new students to school at the time of identification from the Psychologist. The school supports through accompanying teachers who contribute significantly and inform the student activities through a daily report book. The openness of schools in terms of inclusive education plays an essential role in inclusion education.Â Penelitian ini bertujuan untuk menganalisis peran pendidikan inklusi untuk meningkatkan akses pendidikan dan meningkatkan mutu layanan pendidikan bagi Anak Berkebutuhan Khusus (ABK) sebagaimana amanat dari Permendiknas Nomor 70 tahun 2009. Penelitian ini menggunakan metode deskriptif analitis dengan pendekatan studi kasus di SD Sains Al Biruni Bandung sebagai sekolah inklusi pertama di kota Bandung. Hasil penelitian menunjukkan bahwa: Pertama, peran serta dan dukungan orang tua dapat terlihat pada proses penerimaan siswa baru di sekolah pada saat identifikasi dari Psikolog. Kedua, adanya dukungan sekolah melalui guru pendamping memberikan kontribusi besar serta informasi mengenai aktivitas siswa melalui buku laporan harian. Ketiga, keterbukaan sekolah dalam hal pendidikan inklusi merupakan peran penting terhadap pendidikan inklusi. Adapun fokus dari penelitian ini adalah pada aspek partisipasi masyarakat yang meliputi partisipasi orang tua dan guru pendamping yang berhubungan secara langsung dengan Anak Berkebutuhan Khusus (ABK).